Diversified bi-static radiometric system for object mapping - Kudriashov, V.E.; Tamash, S.M.; Shmakov, D.S. (Radiotekhnika, 2017)
A variant of improving both the sensitivity and resolution on the path difference in a bi-static radiometric system (RMS) is proposed. Values of the radio brightness temperatures of atmospheric radiation in the 3 mm wavelength band are given in different conditions. An equation is obtained for the range of action of the diversified bi-static RMS for mapping of the Earth surface with allowance for interfering radio brightness temperatures. This makes it possible to provide simulation of the RMS, depending on its technical parameters and characteristics of small-sized objects. The advantage of the BRS is shown for the case in which the Doppler frequency shift is present in the system carriage-target. The variant of the range equation is substantiated at space objects monitoring by orbiting BRS. The obtained equations and figures are presented.